‘Silaturrahim’, Malaysian diaspora and social media - Azian Muhamad Adzmi; Norliza Saiful Bahry (Penerbit Universiti Kebangsaan Malaysia, 2020)
‘Silaturrahim’ is a concept of kinship that is unique to the Malays, regardless of where they are in this world. It is a tradition that involves physical actions, and the development in communication has enabled for this to be translated as part of online communication. Using the qualitative approach, through the combination of focus group discussions and in-depth interviews, involving respondents from a wide range of background, this study was carried out to identify the elements of ‘silaturrahim’ that can be found in social media engagement amongst the diaspora community with a focus on Malaysians who are residing abroad – through the way they communicate with their family members and friends back home, and those who are residing in the same country that they are in, as well as with other Malaysian diaspora communities. The study is focused on the way the Malay diaspora continues the tradition of ‘silaturrahim’ while forming a positive online culture. The research begins with the diaspora providing their insights on the primary purpose of using social media. As a preliminary finding, in general, most of the interviewees agreed that social media is a means to bring the diaspora community together, particularly if there are events taking place near them, especially when their traditional food is served in the events. The social media is also seen as the most convenient way of conveying information amongst them, and sharing of news both from home as well as where they are residing.